IJCM_196A: Exploring the transition from medical students to interns: A leap into clinical practice - Jain Animesh; Bansal Shivam; Bhuyan Satya Sundar; Babu Achsah Sara; Simna TT; Ranjan Pushpa (Wolters Kluwer Medknow Publications, 2024)
Background: The transition from medical student to independent doctor is a crucial phase, marked by a year-long clinical internship in India. Despite this, challenges arise, and stress is common among interns. This study aims to assess the preparedness of interns graduating under the present MBBS curriculum in India and understand the challenges they face during their internship. Methodologyology: This cross-sectional analytical study was conducted in teaching hospitals affiliated with Kasturba Medical College, Mangalore. Interns working in various departments of these hospitals were included in the study. Universal sampling was employed, approaching all available interns during the 14-day study duration. The sampling strategy was non-random, based on convenient sampling. Results: Out of 150 interns, 77 scored well in various aspects of clinical skills. However, discrepancies were observed in specific areas. While 84% demonstrated good history-taking skills, only 55% could effectively discuss medications with patients. Interns displayed lower competence in understanding drug interactions, with only 37 out of 150 scoring well. Communication and teamwork were strong points, with 82 interns effectively working in a multi-disciplinary team. On the contrary, clinical procedures and diagnostic skills showed dismal performance, especially in emergency situations and practical procedures. Conclusion: Interns exhibit strength in communication and teamwork but face challenges in diagnostic skills and clinical procedures. The findings emphasize the need for targeted interventions in specific areas, ensuring a well-rounded preparation for junior doctors. Addressing these challenges will contribute to a smoother transition from medical students to competent healthcare professionals.